LED light source for medical optical coherence tomography with high axial resolution
By using phosphor conversion LEDs combined with semiconductor LEDs and spinel-type phosphors in the OCT system, the high cost and low resolution problems of SLD within the spectral range of medical optical windows are solved, and efficient and stable optical imaging is achieved. Suitable for OCT systems.
Patent Information
- Application Number
- CN202380044493.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-14
AI Technical Summary
The existing ultra-radiation light emitting diodes (SLDs) in the spectral range of medical optical windows have problems such as high cost, limited lifetime, low axial optical resolution and low thermal stability, which is difficult to meet biomedical imaging such as optical coherence tomography ( OCT) demand.
Phosphor conversion LED (pcLED) using a combination of semiconductor LEDs and spinel-type phosphors, through a wavelength conversion structure, including spinel-type phosphors with specific components, designs an efficient emission light source in the 1200nm wavelength region to provide low Effective attenuation coefficient and low light scattering achieve high axial resolution and high reliability.
Achieving low cost, high emission stability with drive and temperature, providing high axial resolution and high infrared emission flux, suitable for OCT systems, reducing system costs and improving its cost efficiency and portability.
Smart Images

Figure CN119317686A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority to U.S. Provisional Patent Application 63 / 355,837, filed on June 27, 2022, which is incorporated herein by reference in its entirety. Background Art
[0003] Semiconductor light emitting diodes and laser diodes (collectively referred to herein as "LEDs") are among the most efficient light sources currently available. The emission spectrum of an LED typically exhibits a single narrow peak at a wavelength determined by the structure of the device and the composition of the semiconductor material from which it is constructed. By appropriately selecting the device structure and material system, an LED can be designed to operate at ultraviolet, visible, or infrared wavelengths.
[0004] The LED may be combined with one or more wavelength converting materials (generally referred to herein as "phosphors") that absorb light emitted by the LED and in response emit light of a longer wavelength. For such phosphor-converted LEDs ("pcLEDs"), the fraction of light emitted by the LED that is absorbed by the phosphor depends on the amount of phosphor material in the optical path of the light emitted by the LED, for example, on the concentration of the phosphor material in a phosphor layer disposed on or around the LED and the thickness of the layer.
[0005] Phosphor-converted LEDs can be designed so that all of the light emitted by the LED is absorbed by one or more phosphors, in which case the emission from the pcLED is entirely from the phosphors. In this case, for example, the phosphor can be selected to emit light in a narrow spectral region that is not efficiently generated directly by the LED. Alternatively, the pcLED can be designed so that only a portion of the light emitted by the LED is absorbed by the phosphor, in which case the emission from the pcLED is a mixture of light emitted by the LED and light emitted by the phosphor. By appropriately selecting the LED, phosphor, and phosphor composition, such a pcLED can be designed to emit, for example, white light having a desired color temperature and desired color rendering properties.
[0006] For biomedical imaging methods such as optical coherence tomography (OCT), high-intensity light sources with broadband emission within the medical optical window spectral range (~800-1300nm) are required. Superluminescent diodes (SLDs) applied in commercial systems emit in the desired wavelength range, but show significant limitations due to high cost, limited lifetime, low axial optical resolution (>10μm typical), and low thermal stability of emission. Summary of the invention
[0007] The present specification discloses pcLEDs that can outperform SLDs in all aspects: low cost, high stability of emission over drive and temperature, and high reliability. These pcLEDs can have an emission peak position in the 1200 nm wavelength region, which results in a low effective attenuation coefficient in biological tissue perfused with blood, and low light scattering. For example, the emission peak may have a full width at half maximum (FWHM), which results in a high OCT axial resolution of 3-4 μm. In addition, short wavelength infrared (SWIR) emission flux levels that exceed those of SLDs can be obtained.
[0008] The pcLED disclosed herein comprises a semiconductor LED and a wavelength conversion structure, wherein the wavelength conversion structure comprises a semiconductor LED having a general formula AE 1-x-z A z+0.5(x-y) D 2+0.5(x-y)-z-u E z O4:Ni y ,Cr u A spinel phosphor, wherein AE = Mg, Zn, Co, Be or a mixture of divalent atoms from the group, A = Li, Na, Cu, Ag or a mixture of monovalent atoms from the group, D = Ga, Al, B, In, Sc or a mixture of trivalent atoms from the group, and E = Si, Ge, Sn, Ti, Zr, Hf or a mixture of tetravalent atoms from the group; wherein 0 ≤ x ≤ 1, 0 <y≤0.1,0≤z≤1,0≤u≤0.2。
[0009] The preferred phosphor system is defined by x=1, z=0, A=Li, D=Ga, Al: i.e. Li 0.5-0.5y D 2.5-0.5y-u O4:Ni y ,Cr u , where 0 <y≤0.1,0≤u≤0.2。
[0010] For biological tissue OCT with a spectral width (FWHM) in the range of 180-200nm or 180-230nm or 170-240nm, these spinel phosphors have peak emission in the preferred range of 1100-1300nm, enabling axial imaging resolution in the range of 3-3.2μm. The infrared output power of pcLEDs containing these phosphors in the range of 1000-1700nm can exceed 60mW or exceed 100mW when driven by 1 watt of electrical power delivered to a blue emitting LED.
[0011] The wavelength conversion structure as disclosed herein may include the spinel phosphor disclosed herein in powder form dispersed in a binder such as a silicone binder. Alternatively, the wavelength conversion structure as disclosed herein may include the spinel phosphor disclosed herein in ceramic form.
[0012] The pcLED disclosed herein may optionally include a phosphor that absorbs light emitted by the semiconductor LED and emits light absorbed by the spinel phosphor to provide the desired SWIR emission. In the absence of such an additional phosphor, the (e.g., blue) semiconductor LED emission directly excites the emission from the spinel phosphor to provide the desired SWIR emission.
[0013] This specification also discloses a light source for OCT, an OCT system, and an OCT method using the pcLED disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1A An example OCT system is shown.
[0015] Figure 1B One embodiment of a wavelength conversion structure as part of a lighting device is shown.
[0016] Figure 2 Another embodiment of a wavelength conversion structure as part of a lighting device is shown.
[0017] Figure 3 It is a cross-sectional view of an LED.
[0018] Figure 4 is a cross-sectional view of a device with a wavelength conversion structure in direct contact with an LED.
[0019] Figure 5 is a cross-sectional view of a device with a wavelength conversion structure adjacent to an LED.
[0020] Figure 6 is a cross-sectional view of a device having a wavelength conversion structure spaced apart from an LED.
[0021] Figure 7 The obtained Li 0.532 Ga 2.35 Sc 0.1 O4:Ni 0.051 X-ray powder diffraction (XRD) pattern (Cu kα radiation).
[0022] Figure 8 The obtained Li 0.532 Ga 2.35 Sc 0.1 O4:Ni 0.051 Powder reflection spectrum and emission (620nm excitation) spectrum.
[0023] Fig. 9 The obtained Li 0.536 Al 1.01 Ga 1.44O4:Ni 0.051 X-ray powder spectrum (Cu kα radiation).
[0024] Fig.10 The obtained Li 0.536 Al 1.01 Ga 1.44 O4:Ni 0.051 Powder reflection spectrum and emission (620nm excitation) spectrum.
[0025] Fig.11 The obtained Li 0.273 Mg 0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 X-ray powder spectrum (Cu kα radiation).
[0026] Fig.12 The obtained Li 0.273 Mg 0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 Powder reflection spectrum and emission (620nm excitation) spectrum.
[0027] Fig.13 The obtained Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 X-ray powder spectrum (Cu kα radiation).
[0028] Fig.14 The obtained Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Powder reflection spectrum and emission spectrum (for 620nm excitation).
[0029] Fig.15 The obtained Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Thermal quenching behavior of emission under 620 nm excitation.
[0030] Fig.16 The obtained Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr0.05 X-ray powder spectrum (Cu kα radiation).
[0031] Fig.17 The obtained Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Powder reflection spectrum and emission spectrum (for 620nm excitation).
[0032] Fig.18 The emission spectra of the phosphor-converted LED of Example 8 in the visible (left) and IR (right) spectral ranges are shown.
[0033] Fig.19 The total emission spectrum of the pcLED of Example 7 is shown.
[0034] Fig. 20 The total emission spectrum of the pcLED of Example 8 is shown.
[0035] Fig.21 A SEM micrograph of the surface of Example 9 is shown.
[0036] Fig. 22 The reflectance spectrum of Example 9 is shown.
[0037] Fig.23 The emission spectrum of the pcLED of Example 10 is shown. DETAILED DESCRIPTION
[0038] As described above, the present specification discloses spinel-type phosphors that can be advantageously employed in light sources for medical OCT. OCT is an interferometric optical imaging method that can be used to create three-dimensional images of tissues. OCT can be performed in the frequency domain or in the time domain.
[0039] A detailed review of OCT can be found in https: / / www.ncbi.nlm.nih.gov / pmc / articles / PMC5418377 / turn up.
[0040] refer to Figure 1A, the example OCT system 110 is configured as an interferometer including a low coherence (i.e., broadband) light source 112, which provides light to a sample arm 122 and a reference arm 124 through an optical fiber 114, an optical coupler / splitter 116, and optical fibers 118 and 120. The light transmitted into the sample arm is scattered by the sample in the sample arm and returns to a detector 128 through the optical fiber 118, the optical coupler / splitter 116, and the optical fiber 126. The light transmitted into the reference arm is reflected back by a moving or stationary reflector and returns to the detector 128 through the optical fiber 120, the optical coupler / splitter 116, and the optical fiber 126. The reflected light from the reference arm and the backscattered light from the sample arm interfere at the detector, which produces a corresponding electrical signal. The interference signal from the detector provides information about the structure of the sample from which the light is backscattered.
[0041] The characteristics of the light source in an OCT system is an important design parameter because the axial resolution (also called depth resolution or coherence gate) is the coherence length of the light source (an intrinsic parameter of the light source), which is inversely proportional to its spectral bandwidth. When the spectral distribution of the light source is Gaussian, the axial resolution Δz is given by: Δz = 2ln2 / p*l0 2 / FWHM, where λ0 and FWHM are the light source center wavelength and its bandwidth. Therefore, to achieve high axial resolution, a broadband light source is required. By using a light source with a very large spectral bandwidth, axial resolution in the micrometer and submicrometer range can be achieved.
[0042] Alternatively, a frequency domain OCT system may employ a wavelength tunable light source, such as, for example, a tunable laser or a broadband light source used with a tunable wavelength selective element.
[0043] The wavelength range of a light source suitable for OCT should lie within the "optical window" in the near-infrared (NIR) range of the spectrum, because light in the range of ˜700-1300 nm has a long penetration depth in biological tissue. Oxygenated hemoglobin in the blood strongly absorbs shorter wavelengths, and water strongly absorbs longer wavelengths. In particular for biological tissues perfused with blood (such as skin), the wavelength range of 1100-1300 nm is suitable, also because the scattering coefficient drops significantly at larger wavelengths.
[0044] The present description provides a broadband light source for OCT that mitigates the disadvantages of prior art light sources. The disclosed OCT LED light source can, for example, show an axial resolution in the range of 2.9-3.8 μm for emission peak positions in the range of 1200-1250 nm, and a spectral half width FWHM in the range of 170-240 nm.
[0045] A particular advantage of the disclosed OCT LED light source is that, due to its compact size and the required low-cost driving electronics, it allows for the first time to build cost-effective and even portable OCT systems. The disclosed light source is suitable for both time-domain and frequency-domain OCT systems.
[0046] Composition of spinel SWIR phosphors
[0047] Spinel has the general formula XY2O4, where X is a divalent cation and Y is a trivalent cation (e.g., MgAl2O4), and crystallizes in the cubic (equiaxed) crystal system. The spinel structure is a cubic close-packed oxide with eight tetrahedral sites and four octahedral sites per formula unit. The tetrahedral space is smaller than the octahedral space. Y 3+ ions occupy half of the octahedral cavity, and X 2+ ions occupy one eighth of the tetrahedral cavities. The inverse spinel structure has a different cation distribution because all X 2+ ions and half of Y 3+ ions occupy the octahedral sites, while the other half of the Y 3+ The ions occupy tetrahedral sites. Most spinel structures are between the normal spinel structure and the inverse spinel structure.
[0048] The composition of a spinel can have X=AE ("AE" is an alkaline earth metal) with a charge of +2 and a Y cation with a charge of +3. However, if X is a cation with a charge of +1 and Y is a cation with a charge of +4, a spinel structure is also formed.
[0049] The composition of the spinel SWIR phosphor emitting light in the range of 1000-1700nm can be AE 1-x- z A z+0.5(x-y) D 2+0.5(x-y)-z-u E z O4:Ni y ,Cr u , wherein AE = Mg, Zn, Co, Be or a mixture from the group of divalent atoms, A = Li, Na, Cu, Ag or a mixture from the group of univalent atoms, D = Ga, Al, B, In, Sc or a mixture from the group of trivalent atoms, and E = Si, Ge, Sn, Ti, Zr, Hf or a mixture from the group of tetravalent atoms; wherein 0 ≤ x ≤ 1, 0 <y≤0.1,0≤z≤1,0≤u≤0.2。
[0050] The composition of the spinel SWIR phosphor may have x=1 and z=0 (i.e., no AE atoms and no E atoms) and A=Li and D=Ga and Al, Sc, or a mixture of Al and Sc, where Ga is the main component of D (i.e., has a higher concentration than Al and / or Sc). A preferred phosphor system for an OCT light source is defined by x=1, z=0, A=Li, D=Ga, Al: Li 0.5-0.5y D 2.5-0.5y-u O4:Ni y ,Cr u , where 0 <y≤0.1,0≤u≤0.2。
[0051] The composition of the SWIR phosphor can have A atoms and D atoms (such as Li and Ga) replaced by AE atoms (such as Mg) (A+D is replaced by 2AE to maintain charge neutrality), which the inventors have found to result in a broadening of the emission band and an increase in emission intensity at lower energies. Replacing some of the A atoms (such as Li) with AE atoms (such as Mg) can be done without significant changes in properties (x<1). Zn can reduce the optical band gap and luminous efficiency. Co has about the same size as Mg, Zn or Li and also shows IR emission. The E atom can be Ge, as it is known to form an inverse spinel structure with, for example, Li and Ga, which are also present.
[0052] An example of a spinel-type SWIR phosphor is the inverse spinel phosphor Li 0.475 AlGa 1.475 O4:Ni 0.05 and Li 0.225 Mg 0.5 Ga 2.225 O4:Ni 0.05 , where D cations Ga and Al occupy the tetrahedral and octahedral sites of the spinel structure. The emission of these phosphors is located in the 1100-1600nm wavelength range. The absorption and emission bands of these phosphors can be adjusted by changing the average size of the D cations. The inventors found that D cations larger than Ga (such as In or Sc) cause spectral red shifts, while cations smaller than Ga (such as Al or B) cause spectral blue shifts of the absorption and emission bands.
[0053] These inverse spinel SWIR phosphors are similar to Cr 3+ Co-doping of Cr allows efficient excitation in the blue and red spectral range. 3+ ions absorb most of the excitation energy and transfer it to the Ni 2+ atoms, the latter showing broadband luminescence in the wavelength range of 1100-1600nm. An example of such a phosphor component is Li 0.49 Sc 0.05 Ga 2.384 O4:Ni0.013 ,Cr 0.05 .
[0054] In the method for synthesizing spinel-type SWIR phosphor compositions, a flux additive may be used. The flux additive used for the inverse spinel phosphor herein may be a borate compound, such as lithium tetraborate Li2B4O7. When such a flux additive is used, a small amount of boron may be present in the SWIR phosphor after full processing, and such boron may improve the luminous intensity.
[0055] Light source including a spinel-type SWIR phosphor
[0056] Figure 1B A wavelength conversion structure 108 is shown that includes at least one of the disclosed luminescent SWIR spinel phosphors. The wavelength conversion structure 108 is used in an illumination device 101 that includes a primary light source 100. The illumination device 101 can be used as a light source for an OCT system as described above. Within the device 101, the primary light source 100 can be an LED or any other suitable light source, including, for example, a resonant cavity light emitting diode (RCLED) and a vertical cavity laser diode (VCSEL). The light source 100 emits a first light 104. A portion of the first light 104 is incident on the wavelength conversion structure 108. The wavelength conversion structure 108 absorbs the first light 104 and emits a second light 112. The wavelength conversion structure 108 can be configured so that little or no first light is part of the final emission spectrum from the device, although this is not required.
[0057] The primary light source 100 may emit blue light and may be or include, for example, an InGaN LED. Alternatively, the primary light source 100 may emit light of a longer wavelength, such as, for example, red light, and may be or include an AlInGaP LED.
[0058] The wavelength conversion structure 108 may include a SWIR phosphor that can be excited in the red spectral range. In this case, the device 101 may include a red emitting LED as the primary light source 100, which emits a first light 104 in the wavelength range of 600-1000 nm. In some embodiments, the light source 100 is an AlInGaP type emitter and can emit the first light 104 in the wavelength range of 600-650 nm. In other embodiments, the light source 100 may be an InGaAs type emitter and can emit the first light in the wavelength range of 700-1000 nm to directly excite the disclosed doped Ni via the absorption transition at the lowest energy. 2+ SWIR phosphors.
[0059] In one example, device 101 may have a wavelength conversion structure 108 including Li0.5-0.5x (Ga,Sc) 2.5-0.5x-y O4:Ni x ,Cr y (where 0 ≤ x ≤ 1, 0 < y ≤ 0.1, 0 ≤ z ≤ 1, 0 ≤ u ≤ 0.2) a spinel-type SWIR phosphor, and an AlInGaP-type LED emitting at 620 - 630 nm can be used as the primary light source 100. More specifically, the device 101 can have a wavelength conversion structure 108, and the wavelength conversion structure 108 includes Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 a spinel-type SWIR phosphor, and an AlInGaP-type LED emitting at 622 nm can be used as the primary light source 100.
[0060] The wavelength conversion structure 108 described with respect to FIG. 1 can be fabricated, for example, in the form of a powder, a ceramic, or any other suitable form. The wavelength conversion structure 108 can be formed as one or more structures that are formed separately from and can be disposed separately from the light source, such as prefabricated glass or ceramic tiles; or can be formed as a structure that is formed in situ with the light source, such as a conformal coating or other coating formed on or above the light source.
[0061] In some embodiments, the wavelength conversion structure 108 can include a powder dispersed in, for example, a transparent matrix, a glass matrix, a ceramic matrix, or any other suitable material or structure. The SWIR phosphor dispersed in the matrix can, for example, be segmented or formed into tiles disposed above the light source. The glass matrix can be, for example, a low melting point glass with a softening point below 1000 °C, or any other suitable glass or other transparent material. The ceramic matrix material can be, for example, a fluoride salt (such as CaF2) or any other suitable material.
[0062] The wavelength conversion structure 108 can be used in powder form, for example, by mixing the powdered SWIR phosphor with a transparent material (such as silicone resin) and dispensing or otherwise disposing it in the optical path. In powder form, the average particle size (e.g., particle diameter) of the SWIR phosphor can be at least 1 μm in some embodiments, not more than 50 μm in some embodiments, at least 5 μm in some embodiments, and not more than 20 μm in some embodiments. In some embodiments, each SWIR phosphor particle or powdered SWIR phosphor layer can be coated with one or more materials, such as silicates, phosphates, and / or one or more oxides, for example, to improve absorption and luminescence properties and / or to increase the functional lifetime of the material.
[0063] The phosphor in powder form can be mixed, for example, with a curable phenylmethylpolysiloxane resin or dimethylpolysiloxane resin to form a phosphor in a silicone suspension, which can be cast into a film after film curing and cutting to form a converter component, or can be directly dispensed into an LED package equipped with, for example, an InGaN LED die emitting in the wavelength range of 420-450 nm. The powder phosphor can also be used to coat at least a portion of an optical fiber element that is optically coupled to a pump light source to form an OCT light source.
[0064] Alternatively, and even more preferably, the disclosed spinel phosphor is first fired to obtain a reactive precursor powder which is then sintered into a polycrystalline ceramic. Forming options may be ceramic tape casting followed by tape drying, cutting, stacking, lamination, debonding and sintering to form a free-standing ceramic wafer which can be diced to attach it to, for example, an InGaN-type LED die emitting in the 420-450 nm wavelength range.
[0065] Figure 2 Another embodiment is shown in which a wavelength conversion structure including one or more of the disclosed SWIR phosphor materials can be further combined with a second phosphor system. Figure 2 In FIG. 2 , the wavelength conversion structure 218 includes the SWIR phosphor portion 208 and the second phosphor portion 202 as part of the illumination device 201. The illumination device 201 may be used as a light source for an OCT system as described above.
[0066] exist Figure 2, light source 200 may be an LED or any other suitable light source, including as examples resonant cavity light emitting diodes (RCLEDs) and vertical cavity laser diodes (VCSELs). Light source 200 emits first light 204. First light 204 is incident on a wavelength conversion structure 218, which includes a SWIR phosphor portion 208 and a second phosphor system 202, the SWIR phosphor portion 208 including one or more of the SWIR phosphors disclosed herein. A portion of first light 204 is incident on second phosphor portion 202 of wavelength conversion structure 218. Second phosphor 202 absorbs first light 204 and emits third light 206. Third light 206 may have a wavelength range within the excitation range of the SWIR phosphor in SWIR phosphor portion 208 of wavelength conversion structure 218. Third light 206 is incident on SWIR phosphor portion 208. SWIR phosphor portion 208 absorbs all or part of third light 206 and emits fourth light 210. Additionally, a portion of the first light 204 may be incident on the SWIR phosphor portion 208 of the wavelength conversion structure 218. The SWIR phosphor portion 208 may absorb the first light 204 and emit the second light 212, or the first light 204 may pass through the SWIR phosphor portion 208.
[0067] The wavelength conversion structure 218 including the SWIR phosphor 208 and the second phosphor 202 may be configured such that little or no first light or third light is part of the final emission spectrum from the device, although this is not required.
[0068] The SWIR phosphor portion 208 of the wavelength conversion structure 218 may include, for example, Ni 2+ Spinel phosphor or Ni 2+ and Cr 2+ One or more of the spinel phosphors cause the device 201 to emit light in the wavelength range of 1000-1700 nm.
[0069] Any suitable second phosphor may be used in the second phosphor system 202. The second phosphor system 202 may be used with the SWIR phosphor portion 208 to broaden the spectral range that allows for effective excitation of the SWIR phosphor and, therefore, increase the number of types of primary light sources 200 that may be used in the device 201. That is, the second phosphor system 202 may include a second phosphor that absorbs first light 204 from a primary light source 200 that emits light outside of the wavelength range required to excite the SWIR phosphor. For example, the second phosphor system 202 may absorb first light 204 emitted from a blue or green LED as the primary light source 200. The second phosphor system 202 then emits third light 206 in the red spectral range. The third light 206 emitted from the second phosphor system 202 excites the SWIR phosphor in the SWIR phosphor portion 208.
[0070] For example, device 201 may include a green to red emitting phosphor, such as Eu 2+ Phosphors are added as a second phosphor system 202, and a blue emitting LED may be used as the primary light source 200. Examples of red emitting phosphors for use in the second phosphor system 202 include (Sr, Ca)AlSiN3:Eu and (Ba, Sr, Ca)2Si 5-x Al x O x N 8-x :Eu.
[0071] In an example device, the primary light source 200 may be an InGaN type emitter emitting blue light. The wavelength conversion structure 218 may include a (Ba, Sr) 2 Si 5 N 8 : Eu phosphor emitting orange-red as the second phosphor system 202 and a Li 2 O 2 phosphor as the SWIR phosphor portion 212. 0.5-0.5x (Ga,Sc) 2.5-0.5x-y O4:Ni x ,Cr y Spinel phosphor. In particular, the device 201 may include as primary light source 200 an InGaN type emitter emitting 440-455 nm and a wavelength conversion structure 218 comprising a phosphor (Ba 0.4 Sr 0.6 ) 2-x Si5N8:Eu 0.02 and Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 SWIR phosphors.
[0072] The second phosphor system 202 may include Cr-doped 3+ The phosphor is doped with Cr 3+ The phosphor emits in the 700-1000nm wavelength range and can be excited in the blue to green and red spectral range. 3+ The emission of the phosphor is dominated by the Ni-doped 2+ of SWIR phosphors are reabsorbed.
[0073] The second phosphor system 202 may include other Ni 2+ Phosphor systems. Examples include LaMgGa 11 O 19 :Ni, MgO:Ni, MgF2:Ni, Ga2O3:Ni,Ge, or the composition is RE2AEMg2TV3O 12 :Garonite of Ni (RE=Y, La, Lu, Gd, Nd, Yb, Tm, Er; AE=Ca, Sr; TV=Si, Ge).
[0074] Relative to Figure 2 The described wavelength conversion structure 218 including the SWIR phosphor 208 and the second phosphor 202 can be manufactured, for example, in powder form, ceramic form, or any other suitable form. The SWIR phosphor 208 and the second phosphor 202 can be formed into one or more structures that are formed and can be disposed of separately from the light source, such as prefabricated glass or ceramic tiles; or can be formed into structures formed in situ with the light source, such as a conformal coating or other coating formed on or over the light source.
[0075] The SWIR phosphor 208 and the second phosphor 202 may be mixed together in a single wavelength conversion layer, or formed as separate wavelength conversion layers. In a wavelength conversion structure with separate wavelength conversion layers, the SWIR phosphor 208 and the second phosphor 202 may be stacked so that the second phosphor 202 may be disposed between the SWIR phosphor 208 and the light source, or the SWIR phosphor 208 may be disposed between the second phosphor 202 and the light source.
[0076] In some embodiments, the SWIR phosphor 208 and the second phosphor 202 can be powders dispersed in, for example, a transparent matrix, a glass matrix, a ceramic matrix, or any other suitable material or structure. The phosphor dispersed in the matrix can, for example, be segmented or formed into tiles arranged above the light source. The glass matrix can be, for example, a low melting point glass having a softening point below 1000° C., or any other suitable glass or other transparent material. The ceramic matrix material can, for example, be a fluoride salt (such as CaF2) or any other suitable material.
[0077] The SWIR phosphor 208 and the second phosphor 202 can be used in powder form, for example by mixing the powder phosphor with a transparent material (such as silicone) and dispensing or otherwise placing it in the light path. In powder form, the average particle size (e.g., particle diameter) of the phosphor can be at least 1 μm in some embodiments, no more than 50 μm in some embodiments, at least 5 μm in some embodiments, and no more than 20 μm in some embodiments. In some embodiments, individual phosphor particles or powder phosphor layers can be coated with one or more materials, such as silicates, phosphates, and / or one or more oxides, for example to improve absorption and luminescence properties and / or to increase the functional life of the material.
[0078] As shown in Figure 1 and Figure 2 As shown in , a lighting device may include a wavelength conversion structure, which may be used with, for example, light sources 100, 200. Light sources 100, 200 may be light emitting diodes (LEDs). Light emitted by the light emitting diodes is absorbed by the phosphor in the wavelength conversion structure according to an embodiment and emitted at a different wavelength. Figure 3 An example of a suitable light emitting diode (a blue-emitting III-nitride LED) is shown for use in a lighting device (such as reference Figure 2 The disclosed lighting device) is used in which the SWIR phosphor is combined with a second phosphor that absorbs blue light and emits SWIR light.
[0079] Although in the examples described below, the semiconductor light-emitting device is a Group III nitride LED that emits blue light or UV light, semiconductor light-emitting devices other than LEDs, such as laser diodes and semiconductor light-emitting devices made of other material systems, such as other III-V materials, III-phosphides, III-arsenides, II-VI materials, ZnO or Si-based materials, may be used, for example, depending on the wavelength range required to excite the SWIR phosphor or the combination of the SWIR phosphor and the second phosphor in the wavelength conversion structure.
[0080] Figure 3 A III-nitride LED 1 that can be used in embodiments of the present disclosure is shown. Any suitable semiconductor light emitting device can be used, and embodiments of the present disclosure are not limited to Figure 3 As is known in the art, the device shown in FIG. is formed by growing a III-nitride semiconductor structure on a growth substrate 10. Figure 3The growth substrate is typically sapphire, but can be any suitable substrate, such as, for example, SiC, Si, GaN, or a composite substrate. The surface of the growth substrate on which the III-nitride semiconductor structure is grown can be patterned, roughened, or textured prior to growth, which can improve light extraction from the device. Before or after growth, the surface of the growth substrate opposite the growth surface (i.e., the surface through which most of the light is extracted in a flip-chip configuration) can be patterned, roughened, or textured, which can improve light extraction from the device.
[0081] The semiconductor structure includes a light-emitting or active region sandwiched between an n-type region and a p-type region. The n-type region 16 can be grown first and can include multiple layers of different compositions and doping concentrations, including, for example, preparation layers (such as buffer layers or nucleation layers), and / or layers designed to facilitate removal of the growth substrate (which can be n-type or unintentionally doped), and n-type device layers or even p-type device layers designed to be used for the light-emitting region to effectively emit light with specific optical, material or electrical properties desired. The light-emitting or active region 18 is grown on top of the n-type region. Examples of suitable light-emitting regions include a single thick or thin light-emitting layer, or a multi-quantum well light-emitting region including multiple thin or thick light-emitting layers separated by barrier layers. A p-type region 20 can then be grown on top of the light-emitting region. Like the n-type region, the p-type region can include multiple layers of different compositions, thicknesses and doping concentrations, including unintentionally doped layers or n-type layers.
[0082] After growth, a p-contact is formed on the surface of the p-type region. The p-contact 21 typically includes multiple conductive layers, such as a reflective metal and a protective metal, which can prevent or reduce electromigration of the reflective metal. The reflective metal is typically silver, but any suitable material or materials can be used. After forming the p-contact 21, the p-contact 21, the p-type region 20, and a portion of the active region 18 are removed to expose a portion of the n-type region 16 on which the n-contact 22 is formed. The n and p contacts 22 and 21 are electrically isolated from each other by a gap 25, which can be filled with a dielectric, such as an oxide of silicon or any other suitable material. Multiple n-contact vias can be formed; the n-contact 22 and the p-contact 21 are not limited to vias. Figure 3 The arrangement shown in . As is known in the art, the n and p contacts can be redistributed to form bond pads with a dielectric / metal stack.
[0083] To form electrical connections to LED 1, one or more interconnects 26 and 28 are formed on or electrically connected to n and p contacts 22 and 21. Interconnect 26 is electrically connected to Figure 32. Interconnect 28 is electrically connected to p-contact 21. Interconnects 26 and 28 are electrically isolated from n- and p-contacts 22 and 21 and from each other by dielectric layer 24 and gap 27. Interconnects 26 and 28 may be, for example, solder, stud bumps, a gold layer, or any other suitable structure.
[0084] The substrate 10 may be thinned or completely removed. In some embodiments, the surface of the substrate 10 exposed by the thinning is patterned, textured, or roughened to improve light extraction.
[0085] According to the embodiments of the present disclosure, any suitable light emitting device can be used in the light source. Figure 3 The specific LEDs shown in FIG. Figure 3 The LEDs shown in Figure 4 , Figure 5 and Figure 6 It is shown by box 1 in the figure.
[0086] Figure 4 , Figure 5 and Figure 6 FIG. 1 shows a device combining an LED 1 and a wavelength conversion structure 30. According to the above embodiments and examples, the wavelength conversion structure 30 may be, for example, a wavelength conversion structure 108 including a SWIR phosphor as shown in FIG. 1 , or a wavelength conversion structure 108 including a SWIR phosphor as shown in FIG. Figure 2 The wavelength conversion structure 218 with a SWIR phosphor and a second phosphor is shown in FIG.
[0087] exist Figure 4 In the embodiment, the wavelength conversion structure 30 is directly connected to the LED 1. For example, the wavelength conversion structure can be directly connected to Figure 3 The substrate 10 shown in FIG. 1 is connected to the semiconductor structure, or directly to the semiconductor structure if the substrate 10 is removed.
[0088] exist Figure 5 In the embodiment of the present invention, wavelength conversion structure 30 is disposed near LED 1 but is not directly connected to LED 1. For example, wavelength conversion structure 30 may be separated from LED 1 by adhesive layer 32, a small air gap, or any other suitable structure. In some embodiments, the spacing between LED 1 and wavelength conversion structure 30 may be, for example, less than 500 μm.
[0089] exist Figure 6 In the embodiment of the present invention, the wavelength conversion structure 30 is spaced apart from the LED 1. In some embodiments, the spacing between the LED 1 and the wavelength conversion structure 30 may be, for example, in the order of millimeters. Such a device may be referred to as a "remote phosphor" device.
[0090] The wavelength conversion structure 30 may be square, rectangular, polygonal, hexagonal, circular, or any other suitable shape. The wavelength conversion structure may be the same size as the LED 1 , larger than the LED 1 , or smaller than the LED 1 .
[0091] In some embodiments, other materials may be added to the wavelength conversion structure or device, such as, for example, materials that improve optical performance, materials that promote scattering, and / or materials that improve thermal performance.
[0092] Example
[0093] Example 1) Li 0.532 Ga 2.35 Sc 0.1 O4:Ni0 .051 Synthesis Li was synthesized from powders of lithium carbonate (Alfa Aesar, 99.998%), gallium oxide (Molycorp, UHP grade), scandium oxide (MRE Ltd, 5N), and nickel oxide (Alfa Aesar, 99.99%). 0.532 Ga 2.35 Sc 0.1 O4:Ni 0.051 1.595 g lithium carbonate, 17.914 g gallium oxide, 0.567 g scandium oxide, and 0.301 g nickel oxide were mixed by ball milling and fired twice at 1300° C. with intermediate grinding, subsequent ball milling, washing the powder in water, and finally sieving.
[0094] Obtained Li 0.532 Ga 2.35 Sc 0.1 O4:Ni 0.051 The powder crystallizes in an inverse spinel structure with a cubic lattice constant of And the density is 5.812g / cm 3 .
[0095] Figure 7 The obtained Li 0.532 Ga 2.35 Sc 0.1 O4:Ni 0.051 X-ray powder spectrum (Cu kα radiation). Figure 8 The obtained Li 0.532 Ga 2.35 Sc 0.1 O4:Ni 0.051 Powder reflection spectrum 801 and emission (620nm excitation) spectrum 802.
[0096] Example 2) Li 0.536 Al 1.01 Ga 1.44 O4:Ni 0.051 SynthesisLi was synthesized from powders of lithium carbonate (Alfa Aesar, 99.998%), gallium oxide (Molycorp, UHP grade), aluminum oxide (Baikowski, 4N), and nickel oxide (Alfa Aesar, 99.99%). 0.536 Al 1.01 Ga 1.44 O4:Ni 0.051 1.968 g lithium carbonate, 13.42 g gallium oxide, 5.123 g aluminum oxide, and 0.375 g nickel oxide were mixed by ball milling and fired twice at 1325° C. with intermediate grinding, subsequent ball milling, washing the powder in water, and finally sieving.
[0097] Obtained Li 0.536 Al 1.01 Ga 1.44 O4:Ni 0.051 The powder crystallizes in an inverse spinel structure with a cubic lattice constant of And the density is 5.001g / cm 3 .
[0098] Fig. 9 The obtained Li 0.536 Al 1.01 Ga 1.44 O4:Ni 0.051 X-ray powder spectrum (Cu kα radiation). Fig.10 The obtained Li 0.536 Al 1.01 Ga 1.44 O4:Ni 0.051 Powder reflectance spectrum 1001 and emission (620 nm excitation) spectrum 1002.
[0099] Example 3) Li 0.273 Mg 0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 Synthesis Li was synthesized from powders of lithium carbonate (Merck, PA), magnesium oxide (Merck, PA), gallium oxide (Molycorp, UHP grade), scandium oxide (MRE Ltd, 5N), and nickel oxide (Alfa Aesar, 99.99%). 0.273 Mg 0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 0.935 g lithium carbonate, 1.854 g magnesium oxide, 18.755 g gallium oxide, 0.317 g scandium oxide, and 0.344 g nickel oxide were mixed by ball milling and fired twice at 1100° C. and 1350° C., respectively, with intermediate grinding, followed by ball milling, washing the powder in water, and finally sieving.
[0100] Obtained Li 0.273 Mg0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 The powder crystallizes in an inverse spinel structure with a cubic lattice constant of And the density is 5.178g / cm 3 . Fig.11 The obtained Li 0.273 Mg 0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 X-ray powder spectrum (Cu kα radiation).
[0101] Fig.12 The obtained Li 0.273 Mg 0.5 Sc 0.05 Ga 2.16 O4:Ni 0.05 Powder reflectance spectrum 1201 and emission (620nm excitation) spectrum 1202.
[0102] Example 4) Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Synthesis Li was synthesized from powders of lithium carbonate (Merck PA), gallium oxide (Molycorp UHP), nickel oxide (Sigma Aldrich, 99%), scandium oxide (MRE Ltd, 5N), lithium tetraborate (Alfa Aesar, 98%), and chromium oxide (Alfa Aeasar, >98%). 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 1.517 g of lithium carbonate, 18.654 g of gallium oxide, 0.078 g of nickel oxide, 0.287 g of scandium oxide, 0.176 g of lithium tetraborate and 0.316 g of chromium oxide were mixed by ball milling and fired at 1300°C for 4 hours under ambient conditions. The crude product was ground and washed with dilute hydrochloric acid and water. After sieving, a powder sample crystallized in a cubic spinel structure type with a lattice constant of And the density is 5.769g / cm 3 .
[0103] Fig.13 The obtained Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 X-ray powder spectrum (Cu kα radiation). Fig.14 The powder reflectance spectrum 1601 and emission spectrum (for 620 nm excitation) 1602 are shown, and Fig.15 The obtained Li 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Thermal quenching behavior of emission under 620 nm excitation.
[0104] Example 5) Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Synthesis Li was synthesized from powders of lithium carbonate (Merck PA), gallium oxide (Molycorp UHP), nickel oxide (Sigma Aldrich, 99%), aluminum oxide (Baikowski, >99%), lithium tetraborate (Alfa Aesar, 98%), and chromium oxide (Alfa Aeasar, >98%). 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 1.522 g of lithium carbonate, 18.724 g of gallium oxide, 0.078 g of nickel oxide, 0.213 g of aluminum oxide, 0.176 g of lithium tetraborate and 0.317 g of chromium oxide were mixed by ball milling and fired at 1320°C for 4 hours under ambient conditions. The crude product was ground and washed with dilute hydrochloric acid and water. After sieving, a powder sample crystallized in a cubic spinel structure type with a lattice constant of And the density is 5.779g / cm 3 .
[0105] Fig.16 The obtained Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 X-ray powder spectrum (Cu kα radiation). Fig.17 The obtained Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Powder reflectance spectrum 1901 and emission spectrum 1902 (for 620 nm excitation).
[0106] Example 6) Phosphor-converted LED with red-emitting pump LED The Li synthesized as described in Example 5 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Spinel phosphors and refractive index n d=1.41 and a PDMS type silicone resin with a viscosity of 4 Pa s, and the loading amount relative to the weight of the silicone resin is 220 wt% (i.e., 220 g of phosphor in 100 g of silicone resin, and 69 wt% of phosphor in the silicone resin). The suspension is then dispersed into a 2.7×2.0 mm 2 The lead frame LED package is equipped with an LED die emitting at 622 nm, which emits a radiant power of 195 mW at 350 mA and room temperature.
[0107] Fig.18 The emission spectrum of the phosphor-converted LED of Example 8 in the visible light 2101 and IR 2102 spectral range is shown. Fig.16 The same emission band as shown in , except there is a small dip in the emission profile at about 1190 nm due to absorption by the silicone sealant used. The total IR radiation power emitted in the 1000-1600 nm spectral range is 50-60 mW (power conversion red / IR = 25-30%) ( Fig.21 ).
[0108] Example 7) Phosphor-converted LED with blue-emitting InGaN pump LED Li synthesized as described in Example 5 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 The spinel phosphor was mixed with a polydimethylsiloxane type silicone sealant (phosphor / silicone weight ratio = 0.45) and dispensed into a 2720 type lead frame LED package measuring 2.7 mm × 2.0 mm × 0.6 mm (L × W × H) and equipped with an InGaN die emitting 450 nm (if filled with the same silicone as used in Example 8 above, the output power is 550 mW at 350 mA at 25°C). Fig.19 Shown is the total emission spectrum of the pcLED of Example 9 for a drive current of 350 mA. In the spectral range of 1000-1700 nm, the LED shows an infrared output power of 171 mW.
[0109] Example 8) InGaN pump LED with blue emission and additional orange-red emission (Ba 0.4 Sr 0.6 ) 1.98 Si5N8: Eu 0.02 Phosphor-converted LED Li synthesized as described in Example 5 0.49 Sc 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Phosphor and (Ba 0.4 Sr 0.6 ) 1.98 Si5N8:Eu 0.02The phosphor and polydimethylsiloxane type silicone sealant (phosphor / silicone weight ratio = 0.45, IR phosphor / orange-red phosphor weight ratio = 3) were mixed and dispensed into a 2720 type lead frame LED package with dimensions of 2.7 mm × 2.0 mm × 0.6 mm (L × W × H) and equipped with an InGaN die emitting 450 nm (if filled with the same silicone resin used in Example 8 above, the output power is 550 mW at 350 mA at 25°C).
[0110] (Ba 0.4 Sr 0.6 ) 1.98 Si5N8:Eu 0.02 The phosphor was prepared by mixing BaH2 (Materion, >99%), SrH2 (Materion, >99%), Eu2O3 (Neo, >99.9%) and Si3N4 (UBE, >98%) under inert conditions and firing the mixture twice at 1680°C under forming gas with grinding between the firings. The phosphor was then washed in dilute mineral acid, water and ethanol followed by ball milling. Fig. 20 Shown is the total emission spectrum for Example 10 for a 350 mA drive current. In the spectral range of 1000-1700 nm, the LED shows an infrared output power of 139 mW.
[0111] Example 9) Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 Synthesis of polycrystalline ceramics . 11.11 g lithium carbonate (Merck, PA), 136.96 g gallium oxide (Dowa Electronics, 4N), 0.569 g nickel oxide (Sigma Aldrich, 99%), 1.542 g aluminum oxide (Baikowski, SP-DBM), 2.315 g chromium oxide (Materion, 3N5) and 2.67 g aluminum stearate (AlfaAesar, techn grade) were mixed by planetary ball milling and fired at 850°C for 4 hours. After firing, the precursor powder was ball milled in ethanol with aluminum oxide grinding media until an average particle size in the range of 0.6-0.7 μm was obtained, cast on a mylar film with a polyvinyl butyral binder system, and dried. After peeling off the ceramic tape, the forming steps including cutting, stacking, lamination and binder burnout have been carried out, and then the ceramic green body was fired at 1350°C for 8 hours in an air atmosphere.
[0112] The obtained ceramic wafer showed a polycrystalline structure in which the grains were crystallized in a cubic spinel structure, wherein the lattice constant as measured by X-ray diffraction And the density is 97% (relative to the theoretical density calculated from the lattice constant). Fig.21 The morphology of the as-sintered ceramic (top surface) is shown. Fig. 22 The reflectance spectrum of the as-sintered ceramic is shown.
[0113] Example 10) pcLED comprising the ceramic converter element of Example 9 After dicing the ceramic wafer of Example 9 into chips with lateral dimensions of 1×1 mm and thickness in the range of 150-200 μm, the chips were attached on top of the InGaN primary LED light source by means of a heat-curable silicone resin. Fig.23 The emission spectrum of the pcLED is shown with a peak wavelength at 1200 nm and a spectral width (FWHM) of 186 nm, which allows an axial resolution in the 3-4 μm range in OCT applications.
[0114] The present disclosure is illustrative, and not restrictive. Further modifications will be apparent to those skilled in the art in view of the present disclosure, and are intended to fall within the scope of the appended claims.
Claims
1. A light source for an OCT system, the light source comprising: Light Emitting Diodes; and A wavelength conversion structure comprising a spinel-type luminescent material having a peak emission in the range of 1100-1300 nm and a FWHM in the range of 170-240 nm.
2. The light source of claim 1, wherein the spinel-type luminescent material has a peak emission in the range of 1200-1250 nm.
3. The light source according to claim 1, wherein the spinel-type luminescent material has a chemical formula AE 1-x-z A z+0.5(x-y) D 2+0.5(x-y)-z-u E z O4:Ni y ,Cr u ,in AE = Mg, Zn, Co, Be or a mixture thereof; A=Li, Na, Cu, Ag or a mixture thereof; D = Ga, Al, B, In, Sc or a mixture thereof; E=Si, Ge, Sn, Ti, Zr, Hf or mixtures thereof; and 0≤x≤1,0 <y≤0.1,0≤z≤1,0≤u≤0.2。 4. The light source according to claim 3, wherein the spinel-type luminescent material has a chemical formula Li 0.5- 0.5y D 2.5-0.5y-u O4:Ni y ,Cr u , where 0 <y≤0.1、0≤u≤0.2。 5. The light source according to claim 4, wherein the spinel-type luminescent material has a chemical formula Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 .
6. The light source of claim 1, wherein the wavelength conversion structure comprises the spinel luminescent material dispersed in a binder.
7. The light source of claim 6, wherein the adhesive comprises methyl polysiloxane resin.
8. The light source of claim 6, wherein the adhesive comprises dimethylpolysiloxane resin.
9. The light source of claim 1, wherein the wavelength conversion structure comprises a spinel-type luminescent material in the form of a ceramic.
10. The light source of claim 1, wherein the light emitting diode is an InGaN light emitting diode configured to emit light in the range of 420-450 nm, and the spinel type luminescent material is arranged to absorb blue light and in response emit with a peak emission in the range of 1100-1300 nm and a FWHM in the range of 170-240 nm.
11. The light source of claim 10, wherein the wavelength conversion structure comprises a spinel-type luminescent material in the form of a ceramic.
12. The light source according to claim 11, wherein the spinel-type luminescent material has a chemical formula AE 1-x- z A z+0.5(x-y) D 2+0.5(x-y)-z-u E z O4:Ni y ,Cr u ,in AE = Mg, Zn, Co, Be or a mixture thereof; A=Li, Na, Cu, Ag or a mixture thereof; D = Ga, Al, B, In, Sc or a mixture thereof; E=Si, Ge, Sn, Ti, Zr, Hf or mixtures thereof; and 0≤x≤1,0 <y≤0.1,0≤z≤1,0≤u≤0.2。 13. The light source according to claim 12, wherein the spinel-type luminescent material has a chemical formula Li 0.5- 0.5y D 2.5-0.5y-u O4:Ni y ,Cr u , where 0 <y≤0.1、0≤u≤0.2。 14. The light source according to claim 13, wherein the spinel-type luminescent material has a chemical formula Li 0.49 Al 0.05 Ga 2.384 O4:Ni 0.013 ,Cr 0.05 .
15. The light source of claim 14, wherein the spinel-type luminescent material has a peak emission in the range of 1200-1250 nm.
16. An OCT system, comprising: The light source according to any one of claims 1 to 15; Sample arm; Reference arm; and A detector is arranged to generate an interference signal based on light emitted by the light source and coupled into the sample arm and light emitted by the light source and coupled into the reference arm.
17. The OCT system of claim 16, wherein the light source provides an axial resolution of less than 4 microns.